IOM's Efforts to Combat Human Trafficking in Thailand Through Transnational Advocacy Network (2020–2024) - Putri, Falehah Devi Nismara; Muhammad, Ali (Journal of Islamic World and Politics, 2025)
Human trafficking is an increasingly serious problem in Thailand, making it a country of origin, transit, and destination for many victims. This research aims to explore the role of the International Organization for Migration (IOM) in addressing the issue of human trafficking in Thailand. This research uses the conceptual framework of transnational advocacy networks introduced by Keck and Sikkink. The method used in this research is a descriptive qualitative approach, where the researcher has access to various relevant qualitative data collection techniques in obtaining textual data for study and analysis. This research found that, firstly, information politics is conducted by conveying information to raise public awareness through social media platforms. Secondly, symbolic politics involves symbols and campaigns to raise awareness of the dangers of human trafficking. When leveraging politics through surveillance, advocacy, and the implementation of international standards to pressure the Thai government. Finally, accountability politics focuses on turning government statements into policies that can regulate human trafficking in Thailand. Although IOM has implemented various programs and policies, the number of human trafficking cases continues to increase year after year. Key challenges include corruption at the law enforcement level as well as a lack of evaluation of existing programs. This article makes an important contribution in exploring IOM's role in addressing human rights violations in Thailand, particularly in prevention efforts, victim protection, and challenges faced in implementing policies related to human trafficking.